A-276 Inhibition in Attention-Deficit/Hyperactivity Disorder: Binomial Logistic Regressions of Self-Report and Performance-Based Measures. (17th August 2022) - Amitrano, Nicholas R; Balloun, Bailey; Barwegen, Kearston; DeBoer, Adam B; Pyykkonen, Ben A
Abstract: Objective: This study aims to clarify the relationship between self-report and performance-based measures of cognitive, behavioral, and emotional inhibition in diagnosing attention-deficit/hyperactivity disorder (ADHD) in adults. Current research states performance-based measures account for little unique variance in determining ADHD diagnoses; however, research is based mostly in pediatric populations. Method: 78 participants referred for outpatient neuropsychological evaluation for differential diagnosis of ADHD were used. Binomial logistic regressions were used to explore the predictive relationship of inhibition to ADHD as measured by the Trail Making Test—Part B (TMT-B), discriminability index of the Conners' Continuous Performance Test—Second Edition (CPT-II), and Behavior Rating Inventory of Executive Function—Adult (BRIEF-A) Inhibition subscale. Pearson correlations were calculated to determine linear relationships between measures. Results: BRIEF-A Inhibition subscale was the sole variable of significance (p = .043) when predicting ADHD without co-morbid diagnoses, with the model accurately classifying 60.3% of standalone ADHD diagnoses. Conversely, TMT-B scores were the sole variable of significance (p = .044) when predicting ADHD with co-morbid depression and anxiety, with the model accurately classifying 68.9% of co-morbid diagnoses. No measures significantly predicted ADHD with co-morbid depression or anxiety. Only the BRIEF-A Inhibition subscale and the CPT-II discriminability index held a significant correlational relationship (r = -.225, p = .026). Conclusions: As is consistent with current literature, performance-based cognitive measures contributed little predictive power in diagnosing standalone ADHD in adults. However, TMT-B demonstrated significant predictive power when patients also demonstrated clinically significant depression and anxiety – perhaps suggesting a compound effect. Self-report and performance-based inhibition measures held minimal correlation.